Studying longitudinal trajectories in animal models of psychiatric illness and their translation to the human condition. (January 2016) - Driscoll, Carlos A.; Barr, Christina S.
Highlights: Psychopathological lability can occur via altered impulsivity, reward, and anxiety. Genetic factors that contribute to these traits may be adaptive in certain contexts. Studies in rhesus show how gene variants can moderate response to early environment. OPRM1, 5-HTT, CRH, DRD4, and MAOA variants moderate effects of early experience. Abstract: Many forms of psychopathology and/or psychiatric illness can occur through the pathways of altered environmental sensitivity, impulsivity, social functioning, and anxious responding. While these traits are also heritable, environmental conditions are known to play a critical role. The genetic factors that contribute to these traits may be adaptive in certain contexts, but can – under the environmental conditions commonly faced among modern humans – also be key moderators of risk for psychopathological outcomes. This article will discuss how animal studies inform us of the various environmental mechanisms through which prenatal or early postnatal environmental challenge can produce long-term effects on behavior and will briefly address how pre-copulatory, pre-natal and early postnatal epigenetic effects can contribute to persistent alterations in offspring behavior. Its main focus will be how nonhuman primate studies have helped us to understand how genetic vulnerability factors can moderate responses to early environmental factors, suggesting pathways through which early stress might produce long-term effects, thus pointing to systems that might moderate risk for psychiatric illnesses in humans.